Variasi Ukuran Partikel Sorgum Pada Konversi Pati Sorgum Menjadi Bioetanol Dengan Proses Sakarifikasi Dan Fermentasi Serentak - David Hamonangan; Chairul Chairul; Irdoni HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Sorghum is a resource of grain yield 55-75% starch  composition similar to corn, which is potentially as raw material for production of bioethanol. Research based sorghum bioethanol manufacture carried out using enzymes stargenTM 002 and starch raw materials. The purpose of this study was to determine the concentration of substrate and the best time of fermentation to produce bioethanol. The research method consists of hydrolysis and saccharification processes are aided by enzymes stargenTM 002 followed by a fermentation process using yeast  Saccharomyces cereviceae, ferment at room temperature, pH 4.5, enzymes stargenTM 002 concentration 2.5% and evaporated at a temperature 1000C. substrate concentration used was 40 g/, variable particle size used was 20-40 mesh, 40-60 mesh and 60-80 mesh and time of fermentation pada 30, 36, 42, 48, 54, 60, 66 and 72  hours. The result indicate that the particle size at 60-80 mesh and the optimum time is 48 hours can produce the highest bioethanol concentration of 1.04% (v/v). Keyword: Bioethanol, Enzymes StargenTM 002, Fermentation, Sorghum, Substract Concentrations.